2018
DOI: 10.1093/nar/gky912
|View full text |Cite
|
Sign up to set email alerts
|

Substrate specificity of human apurinic/apyrimidinic endonuclease APE1 in the nucleotide incision repair pathway

Abstract: Human apurinic/apyrimidinic (AP) endonuclease APE1 catalyses the hydrolysis of phosphodiester bonds on the 5′ side of an AP-site (in the base excision repair pathway) and of some damaged nucleotides (in the nucleotide incision repair pathway). The range of substrate specificity includes structurally unrelated damaged nucleotides. Here, to examine the mechanism of broad substrate specificity of APE1, we performed pulsed electron–electron double resonance (PELDOR) spectroscopy and pre-steady-state kinetic analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
53
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(59 citation statements)
references
References 70 publications
4
53
0
2
Order By: Relevance
“…PAGE analysis of product accumulation in the course of the interaction of APE1 with every X-substrate (X = αA, DHU, F-site, or εA as damage) was performed first. Direct registration of product formation helped to rank the efficacy of DNA cleavage as follows: F-site > DHU >> αA > εA, in line with other studies [ 25 , 30 , 33 ].…”
Section: Resultssupporting
confidence: 78%
See 2 more Smart Citations
“…PAGE analysis of product accumulation in the course of the interaction of APE1 with every X-substrate (X = αA, DHU, F-site, or εA as damage) was performed first. Direct registration of product formation helped to rank the efficacy of DNA cleavage as follows: F-site > DHU >> αA > εA, in line with other studies [ 25 , 30 , 33 ].…”
Section: Resultssupporting
confidence: 78%
“… Changes in the FRET signal during the interaction of APE1 with each FRET-X-substrate in the absence “−” or presence “+” of 5.0 mM Mg 2+ . FRET traces of the interaction of APE1 with the FRET-F- and FRET-DHU-substrates in the absence of Mg 2+ have been reported earlier [ 25 ]. …”
Section: Figurementioning
confidence: 78%
See 1 more Smart Citation
“…APE1 catalyzes the cleavage of AP- and 5,6-dihydrouridine (DHU)-containing substrates in the same active site ( Felix and Silveira, 2011 ). Moreover, molecular dynamics simulations showed that the broad substrate specificity of APE1 is due to DNA distortion induced by the enzyme, which flips damaged nucleotides into the active site pocket ( Kuznetsova et al, 2018 ). DrXth lacks NIR activity, similar to most prokaryotic ExoIII-like enzymes (e.g., EcXth and MtbXthA).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, human AP endonuclease is versatile in terms of the functions it plays in the cell. Structural data, kinetic studies and a mutation analysis have made it possible to identify the key stages of interaction between APE1 and damaged DNA harboring the AP site [ 15 , 16 , 17 ], as well as some damaged [ 18 ] and undamaged [ 7 ] nucleotides. Kuznetsova et al have suggested a mechanism for the broad substrate specificity of AP endonuclease exhibited upon its interaction with DNA [ 18 ].…”
Section: Introductionmentioning
confidence: 99%